(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2024)
This article takes up the issues of migration and refugeeism, which figure prominently in Pope Francis’ 2014–2023 Messages. It is a topic in its own right, but in fact part of the narrative of poverty, injustice and suffering – aspects of the Pope’s particular concern. In the analyses of the problem, the macro-structural background of the phenomenon is shown, reference is made to current data, but also an indication of the percentage of population flow approved from the point of view of migration movements. In the context of the analysed Messages of Pope Francis, the article addresses the problem of the Pope’s pedagogical stance, which in the texts includes clear indications addressed to the international community on the vision of freedom of movement, the necessity to welcome and unconditionally safeguard the rights and interests of migrants. The principle of inclusivity in the reception of refugees required of states is extended by the Pope to religious inclusivity, and its requirements contain some contradictions, such as preserving separateness while promoting unity.